On the inefficiency of negative feedback in Russian morphology L1 acquisition. Issue 5 (October 2019) - Kulinich, Elena; Royle, Phaedra; Valois, Daniel
This study investigates negative feedback effects on inflectional morphology acquisition in Russian. In order to examine the effects of adult feedback on child error elimination and assess the lasting effect of feedback, a series of elicited tasks was conducted with 65 Russian children aged from 3 to 4 years. Twelve verbs which undergo overregularization in the non-past tense resulting from applying the yod /j/-pattern were used as stimuli. The experiment was repeated over four sessions with bi-weekly intervals between sessions 1, 2, 3 and a four-week interval between sessions 3 and 4. Four groups of participants were formed with three types of feedback (Correction, Clarification Question and Repetition), and a control group without feedback. No significant differences were observed between groups with different feedback types, or even without feedback. This finding supports the general hypothesis that negative feedback is not a strong driver of recovery from overregularization errors in verb acquisition.